Optimal unemployment insurance and international risk sharing - Stéphane Moyen; Nikolai Stähler; Fabian Winkler (Deutsche Bundesbank, 2016)
We discuss how cross-country unemployment insurance can be used to improve international risk sharing. We use a two-country business cycle model with incomplete financial markets and frictional labor markets where the unemployment insurance scheme operates across both countries. Cross-country insurance through the unemployment insurance system can be achieved without affecting unemployment outcomes. The Ramsey-optimal policy however prescribes a more countercyclical replacement rate when international risk sharing concerns enter the unemployment insurance trade-off. We calibrate our model to Eurozone data and find that optimal stabilizing transfers through the unemployment insurance system are sizable and mainly stabilize consumption in the periphery countries, while optimal replacement rates are countercylical overall. Moreover, we find that debt-financed national policies are a poor substitute for fiscal transfers.
Keywords: E32; E62; H21; J64; 330; Unemployment Insurance; International Business Cycles; Fiscal Union; International Risk Sharing